Cost-effectiveness analysis of OM-85 vs placebo in the prevention of acute respiratory tract infections (ARTIs) in children that attend day-care centers - Arturo Berber; Blanca Estela Del-Rio-Navarro (Health Economics Review, 2019)
Background: Children that attend day-care centers frequently contract acute respiratory tract infections (ARTIs). ARTIs represent a burden for both children and parents. Systematic reviews on the use of immunostimulants for the prevention of juvenile recurrent ARTIs have provided moderate evidence of efficacy and safety. The aim of the study was to establish whether the immunostimulant, OM-85, was cost-effective in preventing ARTIs in children 2- 6 years old that attended day-care centers or preschools in Mexico. We performed a systematic review to evaluate the efficacy of OM-85. For costs, we assumed an institutional perspective, which included the costs of care and supplies over a study period of six months, during the autumn-winter seasons. We created decision trees and constructed a model to identify pharmacoeconomic parameters. We generated 1000 estimations with the bootstrap method to calculate descriptive statistics of pharmacoeconomic parameters. We evaluated costeffectiveness compared to treatment without immunostimulants. Results: The mean (SD) incidences of ARTIs were 5.59 ± 0.29 without immunostimulants and 2.97 ± 0.32 with OM85, during the study period. The mean (25th, 75th percentile) direct costs of ARTIs were 57.04 (37.11, 76.39) US (US dollars) without immunostimulants and 48.53 (37.35, 58.93) US with OM-85, with a mean increment of - 8.51(- 17. 08, 0.75) US, and a mean cost-effectiveness of - 17.94 (- 36.48, 1.66) US. The direct costs plus the cost of one parent missing work to care for the child with ARTI were 125.76 (102.83, 150.16) US, without immunostimulant and 85.21 (72.15, 98.81) US, with OM-85. The increment was - 40.55 (- 68.29, - 13.95) US, and the cost-effectiveness was - 86.89 (- 142.37, - 29.34) US.Part of the cost reduction was ascribed to the reduced use of medications, particularly antibiotics. Conclusions: Our results were consistent with previous clinical studies conducted in closed institutions in Mexico. OM-85 reduced the number of ARTIs and the frequency of antibiotics use. We concluded that OM-85 was costeffective for preventing ARTIs in children that attended day-care centers, particularly when parental absenteeism was covered by the institutions.
Keywords: 330; Acute respiratory tract infection; Prevention; Day-care-center; Immunostimulant; OM-85